2023
DOI: 10.1021/acschemneuro.2c00785
|View full text |Cite
|
Sign up to set email alerts
|

An S-Shaped Aβ42 Cross-β Hexamer Embedded into a Lipid Bilayer Reveals Membrane Disruption and Permeability

Abstract: The interactions of amyloid oligomers with membranes are known to contribute to cellular toxicity. Numerous in vitro experimental studies reported on the insertion of oligomers of different sizes that can induce cell membrane disruption, extract lipids, and form ion-permeable transmembrane pores. The current repertoire of amyloid-beta (Aβ) membrane-inserted folds that was subject to high-resolution structure NMR spectroscopy and computer simulations is devoid of any cross-β fibrillar structure. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…On the other hand, Nguyen et al established an S-shaped Aβ42 cross-β hexamer that embeds into the lipid bilayer, leading to membrane disruption. 100 Strikingly, how amyloid-β peptide (Aβ) behaves differently in the aqueous phase and the membrane has been recently explored by Fatafta et al 101 They proved that Aβ undergoes a rapid transition from the random coil to β-sheet in the aqueous phase; however, such a transition is not seen in the membrane. Specifically, on the neuronal membrane, they found that Aβ oligomers introduce toxicity to the neuronal membrane by damaging the membrane via hampering the membrane integrity, resulting in severe disruption of the neurons.…”
Section: Interaction Of Single Amino Acid-based Fibrils With Lipid Ve...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Nguyen et al established an S-shaped Aβ42 cross-β hexamer that embeds into the lipid bilayer, leading to membrane disruption. 100 Strikingly, how amyloid-β peptide (Aβ) behaves differently in the aqueous phase and the membrane has been recently explored by Fatafta et al 101 They proved that Aβ undergoes a rapid transition from the random coil to β-sheet in the aqueous phase; however, such a transition is not seen in the membrane. Specifically, on the neuronal membrane, they found that Aβ oligomers introduce toxicity to the neuronal membrane by damaging the membrane via hampering the membrane integrity, resulting in severe disruption of the neurons.…”
Section: Interaction Of Single Amino Acid-based Fibrils With Lipid Ve...mentioning
confidence: 99%
“…Based on the typical trajectory, they concluded that the peptide, prior to its final adsorption on the membrane, undergoes several binding and unbinding sequences, the extent of which mostly depends on the net charge, hydrophobicity, and polarity of the peptides. On the other hand, Nguyen et al established an S-shaped Aβ42 cross-β hexamer that embeds into the lipid bilayer, leading to membrane disruption . Strikingly, how amyloid-β peptide (Aβ) behaves differently in the aqueous phase and the membrane has been recently explored by Fatafta et al They proved that Aβ undergoes a rapid transition from the random coil to β-sheet in the aqueous phase; however, such a transition is not seen in the membrane.…”
Section: Interaction Of Single Amino Acid-based Fibrils With Lipid Ve...mentioning
confidence: 99%
“…In a recent study, the dynamics of an S-shaped Aβ42 cross-β hexamer model inserted into a lipid bilayer membrane were explored by Nguyen and Derreumaux using two atomistic MD simulations, each two microseconds long [70]. The initial model was characterized by the CHC and residues 30-42 embedded into a DOPC bilayer membrane (Figure 2).…”
Section: Amyloid-β Pore Formationmentioning
confidence: 99%
“…View in the x direction, parallel to the fibril axis.We show the ribbon structure of the hexamer, the phosphate atoms (tan), and the O21 and O22 atoms of the glycerol (black). Also shown are the Cα atom of V12 (yellow), Q15 (blue), V18 (orange), E22 (purple), and K28 (red)[70].…”
mentioning
confidence: 99%